Semitransparent Functional Devices using PEDOT and/or ZnO Heterostructures - Rodríguez Moreno, Jorge (Universidad de Málaga, Servicio de Publicaciones y Divulgación Científica, 2014)
This thesis focus on the development of two differentiated devices, using common and interchangeable materials: (1) electronic diodes and (2) electrochemical capacitors, also known as supercapacitors. Special attention was given for these devices to be transparent or at least translucent. This work is proposed as a first step in a way to achieve a single device having shared materials as well as integrating energy generation (solar cells) with storing of the produced energy (supercapacitor). In order to accomplish those challenging goals, ZnO and PEDOT have been selected as common compounds to be used in supercapacitors and diodes. ZnO has been used in two morphologies, as thin film and as arrays of nanorods. ZnO was initially tested as an n-type semiconducting oxide in a diode composed of ZnO nanorods and p+-type Si. Likewise, the performance of PEDOT was evaluated in a semitransparent supercapacitor consisting of two symmetrical PEDOT electrodes with an intermediate layer of ionic polymer of PVP/LiClO4. Later on, both materials were combined to address a heterostructured diode and a supercapacitor electrode. The former was arranged as ZnO/PEDOT film. Whereas, supercapacitor electrode was carried out directly on a ZnO nanorod/CuS/PEDOT conformation decorated with MnO2 nanoparticles, leading to an enhanced energy storage capacity and improving its transparency. CuS improved the electrodeposition of PEDOT on the ZnO nanorods and the charge transfer. This thesis is elaborated by a compendium of scientific articles, structured in four parts. The first is an introduction where every topic is presented, showing the theoretical background and state of the art. Afterwards, a review of every instrument and experimental methodology used is given. The results and the subsequent discussion are displayed in the included copy of the four articles. Finally, a global discussion and conclusions are provided, where a general analysis and abridgement of conclusions of all contributions is shown. --------------- Esta tesis se centra en el desarrollo de dos dispositivos bien diferenciados los cuales comparten materiales comunes y a su vez son intercambiables: (1) diodos electrónicos y (2) condensadores electroquímicos, también llamados supercondensadores. Se ha prestado especial atención en que fuesen transparentes o al menos translucidos. Este trabajo supone un primer paso para desarrollar un dispositivo integrado que presente tanto generación (celda solar) como almacenamiento de energía, compartiendo ciertos materiales. Con la intención de resolver estos objetivos, se ha seleccionado al ZnO y al PEDOT como materiales idóneos para crear tanto un supercondensador como un diodo. Se han elegido dos morfologías para el ZnO, una en forma de capas finas y otra en nanohilos. Inicialmente, se comprobó que el ZnO se comporta como un óxido semiconductor de tipo-n en un diodo heterounión de nanohilos de ZnO pegado a un silicio tipo-p+. En el siguiente artículo, se evaluó el comportamiento del PEDOT en un supercondensador semitransparente compuesto por dos electrodos simétricos unidos por una capa intermedia de PVP/LiClO4. Posteriormente, ambos materiales se combinaron para realizar un diodo heteroestructurado y un electrodo de supercondensador. El primero se desarrolló con capas finas de ZnO/PEDOT. Sin embargo, el electrodo del supercondensador se ha llevado a cabo directamente con una estructura de nanoestructurada: nanohilos de ZnO sobre la que se ha depositado sucesivas capas de CuS y PEDOT decorada con nanopartículas de MnO2. Con ello se ha mejorado sustancialmente la energía almacenada y la transparencia. El uso de CuS mejoró la electrodeposición de PEDOT sobre los nanohilos de ZnO y la transferencia de carga.
Keywords: Física aplicada - Tesis doctorales; ZnO; PEDOT; Semitransparent; Diode; Supercapacitor